Há lugar para a criança falar sobre a morte violenta? As vozes das trabalhadoras do Sistema de Garantia de Direitos da Infância - Maranhão, Joyce Hilário (2022)
This research investigates the non-place of children who witnessed scenes of violent death in the speeches of professionals in the Rights Guarantee System. In order to respond to this objective, the specific objectives are: to identify and analyze the work of professionals involved in the provisions of the Rights Guarantee System; collect propositions related to the clinic and the policy of care for victims of violence; and to perceive, with emphasis on the clinical and social incidences, what are the possible destinations for the child from this experience of loss due to violent death. Therefore, the research was divided into three ways of studying the theme, each one corresponding to some specific objective: 1) systematic literature review, in order to build the theoretical framework of this thesis; 2) extension course with professionals from the Rights Guarantee System, entitled: “The reception of children in contexts of violent death: clinical and institutional devices”; 3) critical analysis of the data collected from the clinical listening of the children and the extension course having Psychoanalysis as an epistemological basis. The thesis brings into play the subjects who still have their mourning forgotten and so little care in society, debating the psychic and social effects of violent death for children in extreme social situations and the work with them in the psychoanalytic clinic and in the institutions of the System of Guarantee of Rights. Beforehand, I point out the observation that there is no literature that presents a place for the child to talk about his experience of loss due to violent death and his mourning, which already explains the originality of the thesis when seeking to listen to the child character and the public social policy workers. Finally, the completion of the course confirmed the hypotheses that this erasure of the child in scenes of violent death is related to the difficulty of adults to recognize the presence of children in such contexts, both due to the traumatic potential of hearing about such a scene by those who occupy this caretaker role both for maintaining the idea that children would not be able to talk about this experience. Still, there was the fear that the intervention with the child could cause more suffering, transferring the child's listening function to the clinical scope.